T Cell Dysregulation in Non-silicotic Silica Exposed Workers: A Step Toward Immune Tolerance Breakdown - Brilland, Benoit; Beauvillain, Céline; Mazurkiewicz, Gery; Rucay, Pierre; Roquelaure, Yves; Tabiasco, Julie; Vinatier, Emeline; Riou, Jérémie; Jeannin, Pascale; Renier, Gilles; Subra, Jean-François; Augusto, Jean-François (Frontiers in Immunology, 2019)
Background. Chronic silica exposure can lead to silicosis, complicated or not by autoimmune diseases (AID). The pathophysiology of silica-induced AID remains not fully understood, especially immune mechanisms that may develop in patients without yet established silicosis. We conducted a prospective clinical study to analyze the impact of crystalline silica (CS) on T cell phenotype and regulatory T cells (Tregs) frequency, as well as on auto-antibodies development in non-silicotic workers exposed to CS. Methods. Workers with moderate to high exposure level to CS and aged between 30 and 60 years-old were considered for inclusion. Peripheral blood mononuclear cells were analyzed by flow cytometry. Auto-antibodies were screened in serum by immunofluorescence. Blood from 42 and 45 healthy subjects (HC) was used as control for T cell phenotype and serum analyses, respectively. Results. Among the 63 included workers exposed to CS, 55 had full data available and were analyzed. Ten were exposed to CS for less than 5 years, 18 for 5 to 10 years and 27 for more than 10 years. The frequency of Tregs (CD4+CD25+CD127–FoxP3+) was significantly lower in CS exposed workers as compared to HC. We found an increased expression of the activation marker HLA-DR on T cells (CD3+, CD4+ and CD8+) of CS exposed workers as compared to HC. Tregs to activated T cells ratio was also lower in exposed subjects. In the latter, HLA-DR expression level and Tregs frequency were significantly associated with CS exposure duration. Serum autoantibody detection was significantly higher in CS exposed workers as compared to HC. Especially, among workers exposed more than 10 years, antinuclear antibodies and ANCA were detected in 44% and 22% among them, as compared to 5% and 2.5% in HC, respectively. Conclusion. This work shows that CS exposure is associated with a decrease of Tregs frequency, an increase of T cell activation status, and a tolerance breakdown against auto-antigens. These results show that alterations of the T cell compartment can be detected early over the course of CS exposure, preceding silicosis development or AID onset.